Risk Dynamics and Profitability in Islamic Banking: Comparative Evidence from Saudi Arabia and the United Arab Emirates - Nadiva Fahriyyah Ayu Dzakirah; Indah Yuliana; Muhammad Sulhan (Jesya, 2026)
This study aims to analyze the influence of credit risk, leverage, and liquidity risk on the profitability of Islamic banks in Saudi Arabia and the United Arab Emirates for the period 2020–2024. This research gap is based on the inconsistency of previous empirical results regarding the impact of liquidity and capital structure on the financial performance of Islamic banks. Both countries were selected because they are the largest Islamic financial centers in the Gulf region with different structural characteristics. Saudi Arabia dominates the retail market, while the UAE excels in digital innovation and sukuk. The novelty of this study lies in the simultaneous comparative analysis approach in these two major markets to test the consistency of profitability determinants under different regulatory authorities. The research method used is a quantitative approach with panel data regression on 10 full Islamic banks. The results show that credit risk has a significant negative effect and leverage has a significant positive effect on profitability, while liquidity risk has no significant effect. This study contributes to the Islamic finance literature by providing a new empirical resolution to the sensitivity of profitability to productive assets, as well as providing a practical reference for bank management and regulators in optimizing leverage limits and credit screening efficiency.